Proteinograma e teores de cobre, ferro e zinco no soro sanguíneo de ovelhas da raça Santa Inês com mastite experimental por Staphylococcus aureus - de Azevêdo Costa, Nivaldo; Simão, Luis Carlos Valeriano; dos Santos, Rogério Adriano; Afonso, José Augusto Bastos; Fagliari, José Jurandir [UNESP]; da Cruz Cardoso, Elyzabeth; Soares, Pierre Castro; de Mendonça, Carla Lopes (FapUNIFESP (SciELO), 2010)
The aim of the present study was to evaluate the effect of Staphylococcus aureus experimentally induced mastitis on proteinogram and serum concentrations of cupper, iron and zinc levels of Santa Ines primiparous ewes. The right mammary gland of ten healthy ewes was inoculated with 1,0×104 UFC/mL of S. aureus. Clinical examination and determination of serum concentrations of proteins by electrophoresis in polyacrylamide gel (SDS-PAGE), cupper, iron and zinc, as well plasma level of fibrinogen were measured before the inoculation (control) and 12h, 24h, 36h, 48h, 60h, 72h, 84h, 96h, 108h, 120h, 132h, 168h, 180h, 288h and 336h after bacteria inoculation. All animals experimentally infected presented clinical mastitis and subsequent loss of mammary gland function. The electrophoretogram allowed the identification of 23 proteins with molecular weights (MW) ranged from 26.000 to 185.000 daltons (Da) including acute-phase proteins, IgG and IgA. A significant increase (P<0,05) in haptoglobin, ceruloplasmin, IgG and IgA concentrations was observed. Antitrypsin and acid glicoprotein concentrations did not alter. The levels of iron and zinc decreased and the cupper concentration increased. A positive correlation between plasma fibrinogen and serum ceruloplasmin (r=0.74), haptoglobin (r=0.62) and IgA (r=0.62) was also identified. Results showed the importance of ceruloplasmin and haptoglobin as acute-phase proteins in ewes with intramammary infections and confirms fibrinogen as an inflammatory marker because its high correlation with specific proteins. The alterations in the serum levels of Cu, Fe and Zn suggest the action of inflammatory mediators triggered by S. aureus.
Proteinogram and serum concentrations of copper, iron and zinc in Santa Inês ewes with Staphylococcus aureus experimentally induced mastitis
Keywords: Acute-phase proteins; Gram positive; Intramammary infection; Oligoelements; Ruminants; SDSPAGE